United States, Top of the World Hotel in Utqiaġvik - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
Sign for Top of the World Hotel. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3